2014
DOI: 10.1186/1999-3110-55-34
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll and carbohydrate metabolism in developing silique and seed are prerequisite to seed oil content of Brassica napus L.

Abstract: BackgroundAlthough the seed oil content in canola is a crucial quality determining trait, the regulatory mechanisms of its formation are not fully discovered. This study compared the silique and seed physiological characteristics including fresh and dry weight, seed oil content, chlorophyll content, and carbohydrate content in a high oil content line (HOCL) and a low oil content line (LOCL) of canola derived from a recombinant inbred line in 2010, 2011, and 2012. The aim of the investigation is to uncover the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 64 publications
0
32
0
Order By: Relevance
“…Considerable total soluble sugar deposition was observed in the early developing silique wall and seed (mainly liquid endosperm) supported the viewpoint these compounds played key roles in maintaining cellular turgidity for their rapid volume expansion (da Silva et al 1997). Another piece of evidence for this inference was the small quantity of lipids accumulated (\350 mg g -1 ) in canola seed though the seed oil content was markedly different at the early stage (Hua et al 2014).…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Considerable total soluble sugar deposition was observed in the early developing silique wall and seed (mainly liquid endosperm) supported the viewpoint these compounds played key roles in maintaining cellular turgidity for their rapid volume expansion (da Silva et al 1997). Another piece of evidence for this inference was the small quantity of lipids accumulated (\350 mg g -1 ) in canola seed though the seed oil content was markedly different at the early stage (Hua et al 2014).…”
Section: Discussionmentioning
confidence: 81%
“…Because silique is the essential photosynthetic organ (Gammelvind et al 1996), rapid catalysis of the photoassimilates is required because release of the small molecular sugar is very important for its volume expansion and transportation into the developing seed. Previous studies reported that rapid growth of silique occurred from initial flowering to 40 DAA (Hua et al 2014). Thus, more carbohydrates accumulation is an essential issue for silique growth, and coordination of the breakdown of sucrose and starch by related enzymes is required to supply enough substrate.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations